1985
DOI: 10.2307/3430096
|View full text |Cite
|
Sign up to set email alerts
|

Use of Monoclonal and Polyclonal Antibodies against DNA Adducts for the Detection of DNA Lesions in Isolated DNA and in Single Cells

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This accumulation was similar to what the authors previously found in a rat model (Podratz et al, 2011b), indicating the conservation of cisplatin-DNA binding interactions. Similar to humans (Baan et al, 1985), cisplatin caused DNA adduct formation. High doses (>50μg/ml) caused decreased animal survival and apoptosis in brain neurons and oocytes.…”
Section: Cisplatin-induced Neurotoxicity In Drosophilamentioning
confidence: 72%
“…This accumulation was similar to what the authors previously found in a rat model (Podratz et al, 2011b), indicating the conservation of cisplatin-DNA binding interactions. Similar to humans (Baan et al, 1985), cisplatin caused DNA adduct formation. High doses (>50μg/ml) caused decreased animal survival and apoptosis in brain neurons and oocytes.…”
Section: Cisplatin-induced Neurotoxicity In Drosophilamentioning
confidence: 72%